Diving into debate: Comparing discussion‐based and single‐presenter journal club formats in a large PM&R department. Issue 1 (23rd November 2021) - Hearn, Sandra L.; Smith, Sean R.
Abstract: Background: Journal clubs in physical medicine and rehabilitation (PM&R) advance the educational mission by uniting colleagues to learn of literature updates, consider clinical applications, practice critical thinking, and engage in lively dialogue and community. Although discussion‐based journal clubs have been shown to enhance quality, a model for their application across a large and clinically diverse department of PM&R has not been described, nor has one been evaluated in comparison to a single‐speaker podium format. Objective: To develop a discussion‐based PM&R department‐wide journal club, present elements of the journal club model in a manner that would enable replication, and assess effectiveness as perceived by participants, compared to the prior (podium‐based, single‐speaker) format. It was hypothesized that a discussion‐based journal club would more effectively achieve educational goals and would be perceived by participants to be of greater quality and value. Design: Pre‐post educational intervention study, using surveys of PM&R resident and faculty participants. Survey items used a 5‐point Likert scale. Unpaired 2‐tailed t ‐tests were used to compare the formats. Setting: A large academic PM&R department. Participants: PM&R faculty, residents, fellows: 26 respondents (preintervention) and 26 respondents (postintervention) out of a total of 94 and 98 people invited to participate, respectively. Interventions: A discussion‐based departmental journal club was designed and implemented, replacing the previous single‐speaker, podium‐based journal club. Main Outcome Measures: Pre‐ and post‐ intervention respondent ratings of (a) journal club quality and value, and (b) effectiveness in achieving specific educational goals. Results: Compared to the traditional format, the discussion‐based format more effectively met the educational objectives, was of higher quality and value as perceived by respondents, and increased desire to attend the activity. Conclusions: This discussion‐based journal club format can serve as a model for academic PM&R programs looking to enhance the educational value of journal club.